Evolution of epithelial morphogenesis: phenotypic integration across multiple levels of biological organization - Horn, Thorsten; Hilbrant, Maarten; Panfilio, Kristen A. (Frontiers in Genetics, 2015)
Morphogenesis involves the dynamic reorganization of cell and tissue shapes to create the three-dimensional body. Intriguingly, different species have evolved different morphogenetic processes to achieve the same general outcomes during embryonic development. How are meaningful comparisons between species made, and where do the differences lie? In this Perspective, we argue that examining the evolution of embryonic morphogenesis requires the simultaneous consideration of different levels of biological organization: (1) genes, (2) cells, (3) tissues, and (4) the entire egg. To illustrate the importance of integrating these levels, we use the extraembryonic epithelia of insects – a lineage-specific innovation and evolutionary hotspot – as an exemplary case study. We discuss how recent functional data, primarily from RNAi experiments targeting the Hox3/ Zen and U-shaped group transcription factors, provide insights into developmental processes at all four levels. Comparisons of these data from several species both challenge and inform our understanding of homology, in assessing how the process of epithelial morphogenesis has itself evolved.